Aflatoxin Exposure-Caused Male Reproductive Toxicity: Molecular Mechanisms, Detoxification, and Future Directions - Dongyun Ye; Zhihui Hao; Shusheng Tang; Tony Velkov; Chongshan Dai (Biomolecules)
Widespread endocrine disorders and infertility caused by environmental and food pollutants have drawn considerable global attention. Aflatoxins (AFTs), a prominent class of mycotoxins, are recognized as one of the key contributors to environmental and food contamination. Aflatoxin B1 (AFB1) is the most potent and toxic pollutant among them and is known to cause multiple toxic effects, including neuro-, nephro-, hepato-, immune-, and genotoxicity. Recently, concerns have been raised regarding AFB1-induced infertility in both animals and humans. Exposure to AFB1 can disrupt the structure and functionality of reproductive organs, leading to gametogenesis impairment in males, subsequently reducing fertility. The potential molecular mechanisms have been demonstrated to involve oxidative stress, cell cycle arrest, apoptosis, inflammatory responses, and autophagy. Furthermore, several signaling pathways, including nuclear factor erythroid 2-related factor 2; NOD-, LRR-, and pyrin domain-containing protein 3; nuclear factor kappa-B; p53; p21; phosphoinositide 3-kinase/protein kinase B; the mammalian target of rapamycin; adenosine 5′-monophosphate-activated protein kinase; and mitochondrial apoptotic pathways, are implicated in these processes. Various interventions, including the use of small molecules, Chinese herbal extracts, probiotic supplementation, and camel milk, have shown efficacy in ameliorating AFB1-induced male reproductive toxicity, by targeting these signaling pathways. This review provides a comprehensive summary of the harmful impacts of AFB1 exposure on male reproductive organs in mammals, highlighting the potential molecular mechanisms and protective agents.